The Influence of Hedonic Shopping and Free Shipping Tagline on Impulsive Buying of Shopee Users : (Case Study on Student of Al-Falah As-Sunniyah University) - Rohman, Mh. Taufiqur; Habibillah, Dovi Iwan Musthofa; Abdeljawad, Islam (Universitas Airlangga, 2025)
This research is motivated by impulsive buying behavior which is felt to be increasing among Shopee users, especially students. One of the factors is hedonic shopping and free shipping taglines. The purpose of this study is to ascertain if hedonic shopping and free shipping taglines have an impact on students at Al-Falah As-Sunniyah University's impulsive Shopee purchases. One hundred students from Al-Falah As-Sunniyah University who use Shopee make up the sample size for this quantitative study, which employs the survey method and probability sampling procedures utilizing the simple random sampling method. Using the statistical program SPSS 25, multiple regression analysis is applied in the data analysis method. The result shows that impulsive purchasing is significantly impacted by hedonic shopping, and the free shipping tagline, both simultaneously or in separate effect. This study adds and increases knowledge about the impulse buying habits of Indonesian students and digital consumer behavior, especially those related to online shopping at Shopee e-commerce, and as a reference for future research. The study's findings also offer valuable information for creating marketing plans that work for Shopee and other e-commerce sites. They also highlight the significance of educating customers about impulsive buying so that platforms can add tools or services that encourage more thoughtful purchases.